PROFIL KUALITAS DAN SIFAT ANTIHIPERGLIKEMIK AIR SEDUHAN TEH BELUNTAS (Pluchea Indica Less) SELAMA PENYIMPANAN - Paini Sri Widyawati; Monika Prahartiwi; Poppy Finike Epifana Tumbol (Journal of Food Technology and Agroindustry, 2023)
Pluchea indica Less tea has been widely produced as a health drink because it contains phytochemical compounds and has biological activities, such as antihyperglycemic. Pluchea tea is usually produced in tea bags and stored in standing pounds made of aluminum foil. Packaged pluchea teas are usually stored at room temperature for a period of time. During storage, the quality and antihyperglycemic properties of brewed water from packaged pluchea tea have not been studied further. Therefore, this study was conducted to determine the quality and antihyperglycemic properties of pluchea tea during storage. The research design used was a Randomized Block Design (RAK) with one factor including storage time consisting of seven treatment levels, namely 0, 2, 4, 6, 10, 14, and 18 weeks. Each treatment was repeated three times. Parameters analyzed included water content, color, turbidity, pH, total acid, phytochemical composition, total phenol content, total flavonoid content, and antihyperglycemic activity (α-amylase and α-glucosidase). The results showed that storage time affected all test parameters, there was a tendency for storage time to decrease the quality and antihyperglycemic activity. Storage up to 18 weeks can reduce the water content of pluchea tea packaged in tea bags and stored in standing pounds. Therefore, the storage of pluchea tea which is packaged in tea bags and stored in standing pounds needs to be considered so that there is no increase in water content to maintain the quality and antihyperglycemic activity.